Cooled Radiofrequency Ablation for Bilateral Greater Occipital Neuralgia - Vu, Tiffany (Hindawi Publishing Corporation, 2014)
This report describes a case of bilateral greater occipital neuralgia treated with cooled radiofrequency ablation. The case is considered in relation to a review of greater occipital neuralgia, continuous thermal and pulsed radiofrequency ablation, and current medical literature on cooled radiofrequency ablation. In this case, a 35-year-old female with a 2.5-year history of chronic suboccipital bilateral headaches, described as constant, burning, and pulsating pain that started at the suboccipital region and radiated into her vertex. She was diagnosed with bilateral greater occipital neuralgia. She underwent cooled radiofrequency ablation of bilateral greater occipital nerves with minimal side effects and 75% pain reduction. Cooled radiofrequency ablation of the greater occipital nerve in challenging cases is an alternative to pulsed and continuous RFA to alleviate pain with less side effects and potential for long-term efficacy.